2018
DOI: 10.29333/ejmste/85110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Visual/Verbal Learning Style on Concentration and Achievement in Mobile Learning

Abstract: This study investigated the relationship between the style, concentration, and achievement of students in terms of visual/verbal learning when learning conceptual knowledge with the use of mobile phones in the classroom. A total of 93 Chinese college students who majored in education participated in this study. Two major results were identified by combining the methods of correlation analysis and ANOVA (oneway, two-way): A significant correlation was found to exist between concentration and the delayed post-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…It is clear from these findings that the mobile-assisted learning environment has a significant positive effect on students' academic achievement. This conclusion is supported by a number of past research, including work by Bahrani (2011), Chen and Li (2010), Hsu, Hwang, and Chang (2013), Hwang, Huang, Shadiev, Ivić and Jakopec (2016), Hwang et al (2014), Kim and Kim (2012), Lu and Yang (2018), Stockwell (2010), Sung, Chang, and Liu (2016), and Sung, Chang, and Yang (2015).…”
Section: Analysis Of Qualitative Datasupporting
confidence: 55%
See 1 more Smart Citation
“…It is clear from these findings that the mobile-assisted learning environment has a significant positive effect on students' academic achievement. This conclusion is supported by a number of past research, including work by Bahrani (2011), Chen and Li (2010), Hsu, Hwang, and Chang (2013), Hwang, Huang, Shadiev, Ivić and Jakopec (2016), Hwang et al (2014), Kim and Kim (2012), Lu and Yang (2018), Stockwell (2010), Sung, Chang, and Liu (2016), and Sung, Chang, and Yang (2015).…”
Section: Analysis Of Qualitative Datasupporting
confidence: 55%
“…Integration of mobile devices to support language practice and facilitate language learning have also extensively investigated. Some studies have found that mobile phones and tablets, when used appropriately, may assist students in improving academic achievement (Huang, Lin & Cheng, 2010;Ivić & Jakopec, 2016;Lu & Yang, 2018). In a meta-analysis, Sung, Chang, and Liu (2016) found that using mobile devices in education had a medium effect size for learning achievement.…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors that can exaggerate the differences between learning methods are students' ability and interest. According to Lu and Yang (2018), some students prefer to receive information from what they hear and say. Respectively, the verbal learning style is more effective and meaningful for them as it allows them to achieve better results.…”
Section: Effectiveness Of Distance/online Learning In Primary Schoolmentioning
confidence: 99%
“…Abdullah et al (2015) reveal that students' performance in elearning environment increase when considering their preference. Similaryly, Lu and Yang (2018) state that a significant correlation exists between learning style and achievement in m-learning. Furthermore, Kim et al (2017) reveal that individuals with a high level of innovativeness enjoy and adopt m-learning.…”
Section: Research Objectivementioning
confidence: 99%